RISE OF ISLAM IN KASHMIR VALLEY - Shabir Ahmad Lone; Mohammad Ishaq Lone (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
Kashmiri Muslims are ethnic Kashmiris who practice Islam and are native to the Kashmir Valley in Indian-administered Kashmir. Sunni Muslims represent almost all of Kashmiri Muslims. They call themselves "Koshur" in their own tongue. The Kashmir Valley was converted to Islam in large numbers in the fourteenth century. Mir Sayyid Ali Hamadani, a Persian Sufi mystic from Hamedan in western Iran, spurred this by reaching Kashmir three times in the 1370s and 1380s with hundreds of pupils, many of whom settled in Kashmir. Invasion of Islam began in the 12th and 13th centuries. The first Quran in Kashmir was calligraphed in 1237 AD by Fateh Ullah Kashmiri, who is understood to have been an Islamic scholar in Kashmir at the time. Bulbul Shah, also known as Syed Sharaf-ud-Din Abdur Rahman Suhrawardi, was the first Muslim missionary to set foot in Kashmir. The current essay emphasizes the expansion of Islam in Kashmir Valley and the significance of renowned Islamic scholars who spread its teachings there.